Of the Mother and the Whore: a depiction of the contemporary socio-political events and their impacts on female identity in Margaret Atwood’s The Handmaid’s Tale and Oryx and Crake - Rahman, Farhin (Brac University, 2020)
This thesis is submitted in partial fulfillment of the requirements for the degree of Bachelor of Arts in English, 2019.